Efforts to Improve Learning Results Applying Health and Safety Work Using the Inquiry Learning Model - Priyadi, Agung (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
This classroom action research aims to improve student learning outcomes through the application of the inquiry model in the process of teaching and learning activities of the basic competencies of Implementing Occupational Health and Safety. The research subjects were students in class X L 1 in the odd semester of the 2018/2019 academic year at SMK Negeri 6 Malang, researchers conducted research using two action cycles. Classroom action research is carried out repeatedly by following predetermined cycle stages so that the objectives of the applied learning model can be achieved. Indicators of improving student learning outcomes can be seen from the increase in learning outcomes obtained by students after experiencing the process of learning activities using the inquiry model. The results of the study stated that the application of inquiry learning models had a positive influence on improving student learning outcomes.Keywords:   Learning Outcomes, Implementing Occupational Health and Safety, Inquiry